New species and a new record of Corylophidae (Coleoptera: Coccinelloidea) from South Korea - Na, Daum; Park, Jong-Seok (Zootaxa, 2026)
The family Corylophidae LeConte (Coleoptera: Coccinelloidea) is a cosmopolitan group, comprising 28 genera and approximately 300 species. In Korea, three genera and six species have been recorded to date. Here, we describe three new species, Arthrolips punctata sp. nov., A. tenuis sp. nov., and Clypastraea longiceps sp. nov., and report Sericoderus brevicornis Matthews, 1890 as a new Korean record. Illustrations of habitus and genitalia, diagnostic characters, and a distribution map are provided.